(3dHGH GdJChjd aj eYGde GdJfRjds - (3YdGA GdOjf Ydj Hf eMeO GdNGRf GdHZOGOj, GdNGRf,J (B741 (3g` s
(3ChdgG (B:s
(3Ydi JhdjO CMOgeG hCfg hGLH abjd Ef cGf GdhQGK cHjQG hLH Ydjg Cf jQVN def MVQ GdbSeI TjA ef GdeGd HbOQ JWjH Hg faSg s
(3BNQgG (B:s
(3fLR GdLRA GdChd ef JaSjQ GdNGRf hjdjg GdLRA GdKGfi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B156s
Keywords: (3GdJaSjQ hYdhe GdbQBfs